Study of customer purchase intention towards green cars in Malaysia / Muhammad Yusaid Mohd Sazali - Mohd Sazali, Muhammad Yusaid (Faculty of Business and Management, 2019)
Green cars seems to be not so popular and having high demand in Malaysia. However, Malaysian often overlooked the important and benefits by supporting green cars as it is helping towards preserving the environmental pollution and preserving the greenhouse effect. The purpose of this study was to determine the significance factor that will influence the customer purchase intention towards green cars in Malaysia. Hence, This study shows the use of the independent variables that will effecting the customer purchase intention towards green cars in Malaysia that consist of the dimension of Theory of Consumption Value(TCV) which are Funtional Value(FV), Social Value(SV) and Emotional Value(EV) that have significantly affects towards the dependent variable. The respondents were 107 respondents who were between 21 - 60 years old. In this study conducted, the finding showed that automotive industries should pay attention to Emotional Value and Social Value as it have the significance result in this study while Functional Value show no significant as it need to be more specific in term of the quality and price based on the past researchers suggestion that they had conducted. This study can be used as a study to be carrying by future research on study of customer purchase intention towards green cars in Malaysia.